Working from home during the corona pandemic: Investigating the role of authentic leadership, psychological capital, and gender on employee performance - Dahyar Daraba; Hillman Wirawan; Rudi Salam; Muhammad Faisal (Cogent Business & Management, 2021)
The Corona Pandemic has forced many organizations to limit human interactions by implementing what so-called Work-from-Home (WFH). This study aims to investigate the role of Authentic Leadership, Psychological Capital, and employees' gender in predicting employees' performance in a public organization in Indonesia during the implementation of WFH. Participants were recruited from a governmental institution under the Minister of Home Affairs in Indonesia. An online survey link was sent to 150 full-time employees via email or virtual groups. There were 116 usable responses included in the data analysis. The results supported the study hypotheses suggesting that employees' perception of leaders' authenticity could directly influence employees' performance or indirectly via employees' PsyCap. The effect of Authentic Leadership on PsyCap was significantly moderated by employees' gender in which female respondents showed a positive and significant impact of Authentic Leadership on their PsyCap. Working from home could have a significant impact on how employees perceive supports from leaders. Drawing from the Gender Role theory and Work/Family Boundary theory, female employees are more likely than their male counterparts to experience resource loss due to work-family interference and demanding household chores when working from home. Discussion, limitations, and future research directions are included.
Keywords: 650; authentic leadership; psychological capital; performance; public Organisation; WFH